(untitled) (Global Journal of Human-Social Science, 2024)
In Latin America, the production of scientific knowledge in the human sciences in general, and sociology in particular, has been characterized by a double concern. On the one hand, the arrival of ideas, concepts and theories from outside the continent continues to cause strangeness as to their relevance and suitability for a different social and economic context. On the other hand, as a way out of this nonconformity, there has been a search for a common epistemological basis about ourselves that would underpin and clarify this singularity. It is argued that an alternative to overcome this uncertainty lies in the Latin America’s condition of dependence, that is, in the specific way in which we are inserted into the world capitalist system, as a fundamental element in understanding or explaining recurring impasses and challenging novelties. In fact, it is about strengthening a fruitful tradition, which has provided us with great insights into countless objects of study.